Fetal hypoxia and hyperglycemia in the formation of phenytoin‐induced cleft lip and maxillary hypoplasia. Issue 3 (29th July 2019) - Ritchie, Helen E.; Oakes, Diana; Farrell, Emma; Ababneh, Deena; Howe, Andrew
Abstract: Objective: Phenytoin exposure during the first trimester of pregnancy increases the risk of maxillary hypoplasia and cleft lip. The etiology of phenytoin embryopathy is unknown. Interestingly, phenytoin is also known to induce hyperglycemia in humans as well as rats. This study uses a rat model of fetal phenytoin syndrome to examine the role of hyperoxia, hyperglycemia, and arachidonic acid deficiency in the development of cleft lip and maxillary hypoplasia. Methods: Pregnant rats were dosed with phenytoin during the critical period of lip development (day 11 of pregnancy) with or without supplemental oxygen, insulin, or arachidonic acid. The fetuses from all studies were examined at term. Results: The frequency of cleft lip and maxillary hypoplasia was reduced by treating dams at the time of phenytoin exposure with either increased oxygen or insulin. However, in fetuses from phenytoin‐treated dams dosed with arachidonic acid, the incidence of severe lip deformities remained the same although there was an increase in normal and mildly affected fetuses. Interestingly, this occurred in embryos from hyperglycemic dams. Significance: Together, the results from these experiments suggest phenytoin‐induced malformations may be a multifactorial process as malformations were not solely linked to a hyperglycemic state of the dam.